Effects of perceived descriptive norms on corrupt intention: The mediating role of moral disengagement. (31st January 2017) - Zhao, Huanhuan; Zhang, Heyun; Xu, Yan
Abstract : The present study attempts to examine the effect of perceived descriptive norms on corrupt intention (e.g., bribe‐taking intention) and then further explore the psychological mechanism underlying this effect. Based on social cognitive theory, we established a mediation model in which moral disengagement partially mediated the link between perceived descriptive norms and corrupt intention. In Study 1, participants ( N = 690) completed a series of questionnaires, and the results demonstrated that, while perceived descriptive norms were positively associated with corrupt intention, it was partially mediated by moral disengagement. In Study 2, we conducted a priming experiment ( N = 161) to test the causal relationship and psychological mechanism between perceived descriptive norms and corrupt intention. The results revealed that perceived descriptive norms triggered the propensity of individuals to morally disengage, which in turn, partially increased their corrupt intention. This study not only extends previous research by providing evidence that moral disengagement may be one of the reasons why perceived descriptive norms facilitate corrupt intention, but also suggests that reshaping normative beliefs and preventing the moral disengagement of individuals may be the effective ways to curb corrupt behaviours.